The system of equations is
![\begin{gathered} -3x+3y=-3\Rightarrow(1) \\ 2x-y=0\Rightarrow(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uv0j07070yw3olmxrbtvvefgea342gfvtr.png)
Since all terms in equation 1 can divide by 3, then
Divide each term in equation 1 by 3
![\begin{gathered} (-3x)/(3)+(3y)/(3)=(-3)/(3) \\ -x+y=-1\Rightarrow(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o4bzne4lo8dk6qecw6w478va9i9ixpfuen.png)
Add equations (2) and (3) to eliminate y
![\begin{gathered} (2x-x)+(-y+y)=(0-1) \\ x+0=-1 \\ x=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/v03kq7fvhog200hya4tv67jx0vkbmm0buz.png)
Substitute x by -1 in equation (2) to find y
![\begin{gathered} 2(-1)-y=0 \\ -2-y=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mdwzuezwhhmi183oyd4u206gg0mxrd17vf.png)
Add y to both sides
![\begin{gathered} -2-y+y=0+y \\ -2+0=y \\ -2=y \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/15qveo245tj3c6li83u7eumjtvza8xraah.png)
The solution of the given system of equations is (-1, -2)